2020
DOI: 10.1080/1047840x.2020.1820214
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Screen Time: Identity Development in the Digital Age

Abstract: We are in the midst of a global transition in which digital "screens" are no longer simply entertainment devices and distractions; rather, adolescents are currently living in a hybrid reality that links digital spaces to offline contexts. Yet, psychological scientists studying the mental health impact of digital experiences largely focus on correlations with "screen time," leading to oversimplified and atheoretical conclusions. We propose an alternative, functional approach to studying adolescent mental health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
112
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(121 citation statements)
references
References 229 publications
(235 reference statements)
1
112
0
8
Order By: Relevance
“…In the decades since these theories above were introduced, SM has become a primary source through which young women receive and transmit information about beauty standards and engage in self-objectification and social comparison. Theoretical perspectives on SM have increasingly moved away from considerations of specific sites or platforms, and instead have emphasized an "affordances" approach-i.e., considering specific facets of SM that impact individuals' experiences (boyd, 2010;Granic et al, 2020;Moreno & Uhls, 2019). The idea that the features of online environments shape individuals' experiences and behaviors has a long tradition in computer-mediated communication (CMC) theories, which rely on the assumption that individual communication patterns are "mediated" by the technological context in which they occur (see Walther, 2011).…”
Section: C Theories Regarding the Features Of Social Mediamentioning
confidence: 99%
See 3 more Smart Citations
“…In the decades since these theories above were introduced, SM has become a primary source through which young women receive and transmit information about beauty standards and engage in self-objectification and social comparison. Theoretical perspectives on SM have increasingly moved away from considerations of specific sites or platforms, and instead have emphasized an "affordances" approach-i.e., considering specific facets of SM that impact individuals' experiences (boyd, 2010;Granic et al, 2020;Moreno & Uhls, 2019). The idea that the features of online environments shape individuals' experiences and behaviors has a long tradition in computer-mediated communication (CMC) theories, which rely on the assumption that individual communication patterns are "mediated" by the technological context in which they occur (see Walther, 2011).…”
Section: C Theories Regarding the Features Of Social Mediamentioning
confidence: 99%
“…However, the framework does not explicitly address all of the conceptual and empirical complexities inherent to understanding SM's influence on body image, depression, and disordered eating. For example, there are likely to be numerous benefits of SM for adolescent girls' mental health-including opportunities for social connection, creative expression, and identity exploration (Granic et al, 2020;Rideout & Robb, 2018).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Narrative identity — a person’s life story that provides them with meaning and coherence — has been theorized to be essential for mental health ( McAdams and McLean, 2013 ). Research on narrative development has shown that those who ascribe more redemptive meaning to suffering in their narrative identity (i.e., negative events are redeemed by causing or being followed by a positive event) have greater mental health and those finding more examples of personal agency over the course of treatment had greater mental health improvements ( McAdams et al, 2001 ; Adler, 2012 ; Adler et al, 2015 ; Granic et al, 2020 ). Relatedly, hope and optimism are negatively associated with depressive symptoms ( Alarcon et al, 2013 ) and Irving et al (2004) showed that increases in hope positively predicted symptom improvement early in treatment.…”
Section: Introductionmentioning
confidence: 99%